(untitled) (Delta Medical College Journal, 2024)
Glanzmann thrombasthenia is a rare inherited bleeding disorder resulting from mutation in platelet membrane glycoprotein (GP) IIb or IIIa leading to impaired platelet function which is characterized by defective platelet aggregation and diminished clot retraction. Glanzmann thrombasthenia patients commonly visit to physician with features of bleeding. Here we discuss about the case of a 32-years-old young female presented with menorrhagia, ecchymosis and occasional gum bleeding. Her coagulation profile was in favor of Glanzmann thrombasthenia. This rare disease has a good outcome if early diagnosis and proper management can be ensured. Delta Med Col J. Jan 2021;9(2): 101-103